Compliance Analysis of zakat tijarah Practice among PC. Persis Lembang Members with the Dewan Hisbah PP Persis Decisions - Fadhil, Ishma (JOURNAL EKONOMI, KEUANGAN, PERBANKAN DAN AKUNTANSI SYARIAH, 2024)
Zakat tijarah (commercial zakat) is a critical instrument in the Islamic socio-economic system, yet its implementation often diverges from formal religious rulings. This study examines the degree of compliance between   zakat tijarah practices among members of the Persatuan Islam (Persis) Lembang Branch and the official decisions issued by the Dewan Hisbah of the Central Board of Persis. Specifically, the research investigates three interrelated dimensions: members' knowledge of the Dewan Hisbah rulings, the operational practice of   zakat tijarah within four autonomous bodies (Persis, Persistri, Pemuda Persis, and Pemudi Persis), and the gap between normative rulings and lived practice. A mixed-methods approach was employed, combining a cross-sectional survey of 30 purposively selected members with semi-structured interviews of six key informants, including branch chairs and a representative of Dewan Hisbah. Quantitative data were analyzed using descriptive statistics and reliability testing, while qualitative data underwent thematic analysis through a constant-comparison technique. The findings reveal an aggregate conformity score of 80%, indicating moderately high alignment, but expose significant divergence on two specific provisions: the absence of nisab (V4.1) and the obligation to pay zakat on unsold inventory (V4.2), which scored 64.7% and 48.7% respectively. Three structural barriers explain this divergence: limited dissemination of Dewan Hisbah rulings, the perceived economic burden of the 2.5% rate on low-margin traders, and the absence of a formal zakat institution at the branch level. The study contributes to the literature on fatwa institutionalization in Indonesian Islamic mass organisations and offers practical recommendations for closing the doctrine-practice gap